Regression analysis on factors affected roundwood production in Malaysia - Iqtie Qamar Laila Mohd Gani; Mohd Sukhairi Mat Rasat; Razak Wahab; Nur Hafizah Ramle; Mazlan Mohamed; Siti Aisyah Nawawi; Amal Najihah Muhamad Nor (2014)
Regression analysis was carried out from a study conducted to determine factors that affected the production of roundwood in Malaysia from year 2001 to 2010 based on data from Food and Agriculture Organization (FAO) Statistic online database, Forestry Department Peninsular Malaysia (FDPM), Malaysia Timber Industry Board (MTIB) and International Timber Tropical Organization (ITTO). The data have been collected regarding to roundwood production volume, consumption volume, import and export volume to determine the factors that influenced the roundwood production in Malaysia among of them. The result show that the roundwood production in Malaysia significantly affected by roundwood consumption and import, where the regression models obtain the relationship between roundwood production with roundwood consumption (p = 0.000) and roundwood import (p = 0.021